Accounting for Gender Production from a Growth Accounting Framework in Sub-Saharan Africa - Fofack, Hippolyte (World Bank, Washington, DC, 2012)
This paper draws on an expanded growth accounting framework to estimate the relative contribution of women to growth in Sub-Saharan Africa. Empirical results show a consistently positive contribution of women to growth in gross domestic product in the region, both during economic downturns and growth spurts. This is despite the absence of any valuation of home-produced goods and informal sector production, which accounts for the bulk of womens production, in national product and income accounts. Women's positive contribution is largely attributed to their increased rates of labor force participation in wage employment and the reduction in the gender gap in education in recent years.